Left–right political orientation fails to explain environmental attitudes of Europeans outside Western Europe: exploring the moderating role of party positions and issue salience - Baranowski, Mariusz; Huber, Robert A.; Jabkowski, Piotr; Szulecka, Julia (My University, 2024)
While conventional wisdom holds that right-wing individuals tend to present more negative attitudes toward environmental protection, McCright and colleagues (2016) find no clear relationship between political ideology and environmental attitudes in Central and Eastern Europe. The reason for this finding remains speculative. Our study expands on this phenomenon by exploring how party competition and, thereby, parties’ focus on a specific issue moderate this ideology-environment link at an individual level across 28 European countries. Using individual level-data from the European Value Study and party-level estimates from the Chapel Hill Expert Survey, our findings emphasize that respondents’ political orientation predicts their environmental attitudes more strongly when their preferred party prioritizes environmental issues. Notably, the left-right connection weakens when parties downplay environmental concerns, revealing why such issues have less impact in Central and Eastern, and Southern European political landscapes. This underscores the contextual boundaries of
Keywords: Environmental protection; left–right political orientation; economic growth; European values study; chapel hill expert survey